(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1 - Su di un critico arretramento nella teoria della giustizia - 2. La possibile riconduzione della giustizia alla ‘logica’ della carità religiosamente orientata - 3. Il pluralismo religioso come ausilio per un più equo e dinamico con-vivere nelle democrazie contemporanee - 4. Sul ritorno a Morgezia, italica matrice del plurale con-sistere di civiltà e culture euro-mediterranee - 5. - Una declinazione mediterranea della giustizia a sostegno delle realtà estromesse dalle “società dell’abbondanza”. Morgezia, Italic matrix of Euro-Mediterranean civilizations ABSTRACT: The essay aims to claim to Calabria - identified with the "italic" name of Morgezia - the role of matrix of the cultures that have spread from the Mediterranean to the entire planet. It would recall that in the current era, characterized by globalization and emergencies induced by socio-environmental degradation and the regurgitation of conflicts, also according to the papal magisterium, the recovery of the most genuine and plural Mediterranean identities can help give again to Europe - of which Calabria is emblematically assumed as a metaphor - the ability to affect international relations in order to determine their more a fair and balanced structure, and therefore more peaceful with and among peoples, even the most “peripheral” and/or neglected ones.